Evaluasi Pembelajaran di Era Digitalisasi - Dwi Nomi Pura; Melia Distri Yeni; Jesi Pitriya; Zuzanti Ulan Dari (Early Childhood Research and Practice, 2026)
The development of information and communication technology has brought significant changes in various areas of life, including in the field of education. One of the most visible changes is the use of digital technology in the learning process and learning evaluation. Learning evaluation is a very important process in educational activities because it functions to determine the level of success of the learning process and the achievement of student competencies. Along with technological developments, learning evaluation systems that were previously carried out conventionally are now starting to switch to digital-based systems. Digital-based learning evaluation utilizes various technological devices such as computers, the internet, learning applications, and other digital platforms. This research aims to analyze the application of digital-based learning evaluation in the educational process and identify the benefits and challenges faced in its implementation. The research method used is a qualitative method with a literature study approach and descriptive analysis. Research data is obtained from various sources such as books, scientific journals, research articles, and educational documents relevant to the research topic. The research results show that digital-based learning evaluation provides various benefits such as time efficiency, ease of data processing, increased objectivity of assessment, and provides faster feedback to students. Apart from that, digitizing learning evaluations also allows teachers to monitor student learning progress in a more systematic and structured manner. However, the implementation of digital-based learning evaluation also faces various challenges such as limited technological facilities and infrastructure, limited digital skills of teachers, and gaps in access to technology among students. Therefore, efforts are needed to increase teacher digital competence as well as support from adequate technological facilities so that digital-based learning evaluation can be implemented optimally in the world of education